The ability of an oral combination of afoxolaner, moxidectin and pyrantel to protect dogs from Borrelia burgdorferi infections transmitted by Ixodes scapularis - Joseph Prullage; Pascal Dumont; Arathy Nair; Manyun Liu; Utami DiCosty; Ricarda Süssenberger (Parasites & Vectors)
Abstract Background Two studies were conducted to determine whether treatment with NexGard® Plus (NP), a combination of afoxolaner, moxidectin, and pyrantel, prevents transmission of Borrelia burgdorferi to dogs by naturally infected Ixodes scapularis. Methods For each study, 20 dogs were randomly assigned to two groups (n = 10/group): NP and negative control. Twenty-eight days post-treatment, each dog was infested with approximately 50 I. scapularis that had a 60% B. burgdorferi infection rate in study 1 and a 38.5% infection rate in study 2. Five days post-infestation, ticks were counted and removed. The B. burgdorferi-specific C6 antibody was tested for using the SNAP® 4Dx® test (IDEXX) and the Lyme Quant C6 test with serum collected before treatment and infestation and 21, 35, 49, 63, and 75 days post-infestation. Skin biopsies were collected 76 days post-infestation and quantitative polymerase chain reaction (qPCR) conducted to detect B. burgdorferi DNA. Results On the day of count and removal, no ticks were found on treated dogs, while control dogs had an average of 25.1 ticks in study 1 and 19.6 ticks in study 2, for efficacy of 100% (P ≤ 0.0001). All dogs were seronegative before infestation. The first dog in the control groups became seropositive 21 days post-infestation in study 1 and 35 days post-infestation in study 2 by the SNAP 4Dx test and by 21 days post-infestation by the Lyme Quant C6 test in both studies. Ten of 10 dogs in the control group in both studies seroconverted by the end of the study. None of the skin biopsies from treated dogs were positive for B. burgdorferi DNA, while at least three of the four skin biopsies from each of the control dogs tested positive at the end of the studies. No clinical signs of Lyme disease were detected in any of the dogs. Conclusions The results of these studies indicate that NexGard® Plus administered at a dose close to the minimum recommended dose of 2.5 mg/kg afoxolaner is effective 28 days after a single treatment in the prevention of B. burgdorferi transmission from naturally infected I. scapularis ticks to dogs. Graphical Abstract